A Summary of Relay Protection-based Simulation for Dynamic Performance and Reliability Assessment - Li, Fei; Zhuyuan, Luochen (Bright Institute, 2023)
As technology advances, electricity has become an essential aspect of both national security and daily life. Ensuring the safety of the power grid is thus of utmost importance. However, in China, research on relay protection models for dynamic simulation of power systems is still in its early stages. Due to this, the control laws of relay protection elements have not been well understood, leading to inadequate handling of system failures. To ensure the safe operation of power systems, it is crucial to first strengthen the grid structure of the power system. This can be achieved through the improvement of elasticity coefficient, reasonable distribution of reserve capacity, and the reinforcement of the adjustment ability of the tie line between major power grids. Additionally, improving the stable reserve of the power grid is essential. To improve the authenticity and reliability of dynamic simulation, it is necessary to establish a set of relay protection models that are consistent with actual relay protection. By doing so, the stability problem in the power system can be accurately analyzed, leading to improved reliability. In this study, a relay protection model was established that reduces the complexity of modeling and can accurately reflect the dynamic characteristics of the power system following interference. This model is significant to the analysis and research of power systems, as it can enhance the understanding of control laws for relay protection elements, leading to improved management of system failures and better overall reliability.